Strategic Human Resource Management in Healthcare: Elevating Patient Care and Organizational Excellence through Effective HRM Practices - Purwadi, P.; Widjaja, Yani Restiani; Junius, J.; Mahmudah, Nisa (Manunggal Halim Jaya, 2024)
Human Resources (HR) are a key factor in the operations and service quality of hospitals. This study aims to analyze the role of HR in enhancing the efficiency and effectiveness of healthcare services in hospitals. The research method used includes a literature review and field surveys of medical and non-medical staff at several hospitals. The results show that effective HR management significantly contributes to increased patient satisfaction, reduced medical errors, and operational efficiency. Additionally, regular training and career development are proven to be effective in improving employee competence and motivation. This study recommends HR management strategies focused on skill enhancement, the use of information technology, and the development of a positive work culture to achieve higher service standards.